UJI SENSITIVITAS EKSTRAK ETANOL DAUN SIRSAK (Annona muricata L.) TERHADAP ISOLAT BAKTERI PLAK GIGI PADA PASIEN POLIKLINIK UPN "VETERAN" JAKARTA SECARA In Vitro PERIODE MARET 2014 - Asiah, (2014)
Dental plaque is one of causes dental health problems. Dental plaque is composed of several bacteria and fungi. To reduce the formation of dental plaque needed antibacterial compounds obtained from plants and sinthetyc. Soursop leaves have antibacterial compounds such as flavonoids, tannins, acittogenins, alkaloids, and saponins. The purpose of this study was to determine the antibacterial activity and inhibition zone of soursop leaf isolated against dental plaque of patient clinic.Research conducted an experimental study using the disc diffusion method. Concentration of ethanol extract of soursop leaf used is 10 %; 20 % ; 30 %; and a positive control mouthwash using bacterial isolates from dental plaque and Streptococcus mutans. Inhibition can be measured from the clear zone formed around the paper disc on media Mueller Hilton agar (MHA). 10% consentration showed the smallest growth inhibition zone, at dental plaque bacteria isolates is 0.97 mm and S. mutans is 4.10 mm. From Kruskall-Wallis test and One-Way Anova test results, there's a differentiation of growth inhibition zone. Test followed by correlation with the results of the relationship between the increase in the concentration of the ethanol extract of the soursop leaves with a large increase in bacterial inhibition test . To find a large significant difference in the inhibition of dental plaque bacteria with bacterial isolates of S. mutans used the unpaired t test with results significantly different inhibition between dental plaque bacteria isolates and S. mutans.